Hubungan antara Set Kesempatan Investasi dengan Kebijakan Pendanaan dan Dividen, serta Leverage Financial - Shanti, .; Wulaningrum, Ratna (Jurnal Widya Manajemen & Akuntansi, 2005)
The objectives of this study are to investigate the association between the investment opportunity set (IOS) values as firm growth proxy and realized firm growth, corporate financing, dividend policies, and leverage financial. Five proxies IOS are used as firm growth indicator such as "market to book value of assets (MVABVA), market to book value of equity(MVEBVE), firm value to book value of property, plant and equipment (VPPE), capital expenditure to book value assets (CAPBVA), and capital expenditure to market value assets (CAPMVA).